Nisyros Volcano The Kos - Yali - Nisyros Volcanic Field (Active Volcanoes of the World,, 2018)
This book presents the first compilation of scientific research on the island of Nisyros, involving various geoscientific disciplines. Presenting a wealth of illustrations and maps, including a geological map of the volcano, it also provides valuable insights into the geothermal potential of Greece. The island of Nisyros is a Quaternary volcano located at the easternmost end of the South Aegean Volcanic Arc. The island is nearly circular, with an average diameter of 8 km, and covers an area of approximately 42 km2. It lies above a base of Mesozoic limestone and a thin crust, with the mantle-crust transition located at a depth of approximately 27 km. The volcanic edifice of Nisyros comprises a succession of calc-alkaline lavas and pyroclastic rocks, as well as a summit caldera with an average diameter of 4 km.&nbs p; Nisyros marks the most recent volcano in the large prehistoric volcanic field between Kos-Yali-Strongyli-Pyrgousa-Pachia-Nisyros, where the largest eruption ("Kos Plateau Tuff") in the history of the eastern Mediterranean devastated the Dodecanese islands 161,000 years ago. Although the last volcanic activity on Nisyros dates back at least 20,000 to 25,000 years, it encompasses an active hydrothermal system underneath the volcano with temperatures of roughly 100°C at the Lakki plain, the present-day caldera floor and 350°C at a depth of 1,550 m. A high level of seismic unrest, thermal waters and fumarolic gases bear testament to its continuous activity, which is due to a large volume of hot rocks and magma batches at greater depths, be tween 3,000 and 8,000 m. Violent hydrothermal eruptions accompanied by major earthquakes occurred in 1873 and 1888 and left behind large, "world-wide unique" explosion craters in the old caldera. Through diffuse soil degassing, the discharge of all hydrothermal craters in the Lakki plain releases 68 tons of hydrothermal-volcanic derived CO2 and 42 MW of thermal energy per day. This unique volcanic and hydrothermal environment is visited daily by hundreds of tourists.